Long‐term kidney transplant survival in patients with continent urinary diversion. (11th September 2017) - Fournier, Romain; Codas‐Duarte, Ricardo; Daily, Theresa; Martin, Xavier; Badet, Lionel; Fassi‐Fehri, Hakim
Abstract : Objectives: To report the long‐term survival of transplanted kidneys in patients with a continent urinary diversion. Methods: Between January 1987 and July 2015, 16 patients with a median age of 37 years (range 21–63 years) underwent kidney transplantation on a continent urinary diversion. A total of 14 patients presented irreversible dysfunction of the lower urinary tract, and two patients had required radical cystectomy because of bladder cancer. All continent urinary diversions were carried out before the transplantation. There were nine Kock pouches, five Mainz pouches, one Mainz neobladder and one Hautmann neobladder. A total of 11 patients had a previous non‐continent urinary diversion. Of the transplants, 14 came from brain‐dead donors and two from related living donors. Results: The median post‐transplantation follow up was 171 months (range 30–298 months). Two patients died, while six patients lost their transplant and resumed hemodialysis. Nine patients (56.2%) were alive with a functional transplant at the end of follow up. The most common allograft complication was acute pyelonephritis, but no graft was lost as a result of urinary diversion complications. The kidney transplant survival rate was 73.3% after 10 years, and 66.6% after 15 years. Among patients who still had a functional transplant at the time of the study, creatinine clearance was >30 mL/min for seven patients and <30 mL/min for two patients. Conclusions: The present study is the longest series to date of renal transplantation on continent urinary diversions. The long‐term outcome shows that the presence of a continent urinary diversion does not reduce transplant survival.